Preparation method of fireproof and heat-insulating carbon fiber and application thereof in fireproof and heat-insulating fabric

CN122976174APending Publication Date: 2026-10-27FUYANG SHIYADI NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611192968.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]为此,本发明提供防火隔热碳纤维的制备方法及其在防火隔热面料中的应用,用以克服现有技术中碳纤维材料制备过程中关键参数无法实时反馈调节,导致配位聚合物结构不完整、碳气凝胶孔分布不均匀以及隔热性能不稳定,且缺乏红外遮蔽功能问题

Benefits of technology

[0017]与现有技术相比,本发明的有益效果在于,通过将聚丙烯腈基共聚物溶解于二甲基乙酰胺制成纺丝原浆,经纺丝拉伸得到纤维原丝,并在含氧气和溴化氢的混合气体中预氧化,基于表面溴含量与预设溴含量的比对结果动态调节辐射温度,克服了传统预氧化温度固定、反应程度不可控的缺陷,使预氧化纤维的梯形结构转化均匀、表面溴含量稳定在目标范围;通过检测预氧化纤维的断裂伸长率确定纺织张力,并基于张力与伸长率的负相关关系纺织成初始布料,同时检测布料表面粗糙度,为后续层压复合提供了匹配依据;通过配位反应中锌-钠浓度比与特征峰面积比的实时监测,动态补加氯化锌或氢氧化钠溶液并调控补加流量与方式,确保了双金属配位聚合物的化学计量比和结构完整性;通过在碳化过程中基于介电常数变化率动态调节升温速率,优化了碳气凝胶的孔隙结构与压缩回弹性能;通过基于表面粗糙度与压缩回弹率加权计算复合系数,并结合纺织张力确定初始复合参数,动态调整层压复合的压力与温度,实现了界面结合质量与气凝胶结构保护的平衡。本发明将预氧化阶段的溴含量、纺织阶段的断裂伸长率、配位阶段的锌钠浓度比与峰面积比、碳化阶段的介电常数变化率、以及复合阶段的表面粗糙度与压缩回弹率作为各工序的调控依据,使前一工序的输出参数直接决定后一工序的输入基准,从而显著提升了防火隔热碳纤维复合材料的防火性、隔热性、红外信号遮蔽功能以及综合防护性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976174A_ABST
    Figure CN122976174A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of special fiber materials, and particularly relates to a preparation method of fireproof and heat-insulating carbon fiber and application of the fireproof and heat-insulating carbon fiber in fireproof and heat-insulating fabric, which comprises the following steps: dissolving polyacrylonitrile-based copolymer in dimethylacetamide and preparing fiber filaments for pre-oxidation; adjusting radiation temperature based on surface bromine content; weaving initial cloth based on textile tension; mixing dimethylacetamide solution, zinc chloride solution and sodium hydroxide solution, determining supplement parameters based on concentration ratio and characteristic peak area ratio, and performing carbonization to obtain carbon aerogel; determining composite parameters based on roughness and resilience, and compositing the initial cloth and the carbon aerogel to obtain carbon fiber composite material. The present application performs linkage control in the whole process from the preparation of the filaments to the finished product, effectively avoids the decline of the heat-insulating performance and the failure of infrared signal shielding caused by incomplete pre-oxidation, coordination structure defects and poor interface bonding, and thus the carbon fiber composite material with stable performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of special fiber materials technology, and in particular to a method for preparing fire-resistant and heat-insulating carbon fiber and its application in fire-resistant and heat-insulating fabrics. Background Technology

[0002] Polyacrylonitrile-based carbon fibers and their composites have become indispensable key structural materials in aerospace, rail transportation, and high-end sports equipment due to their high specific strength, high specific modulus, and heat resistance. However, existing polyacrylonitrile-based carbon fibers mainly focus on mechanical load-bearing capacity and high temperature resistance, and their infrared radiation characteristics have not been effectively controlled, making it difficult to meet the stringent requirements for low detectability in high-temperature or complex thermal environments.

[0003] Chinese Patent Application Publication No. CN117944337A discloses a flame-retardant and heat-insulating composite fiber fabric and its preparation method, as well as its application in fireproof clothing. The relevant technical solution involves blending polyacrylonitrile pre-oxidized fiber, ceramic fiber, and carbon fiber to form a fireproof layer; then blending polyacrylonitrile pre-oxidized fiber with carbon fiber to form a blended layer, and coating it with a modified polyimide composite coating to form a heat-insulating layer; finally, quilting and sewing it with an aramid nonwoven comfort layer to obtain a composite fabric. The preparation process of modified polyimide includes: first, preparing an intermediate by ring-opening reaction of (3,4-dihydro-2H-1,4-benzoxazine-2-ylmethyl)dimethylamine and 5,6-epoxyhexyltriethoxysilane; then preparing a modified diamine by esterification reaction of the intermediate with 6,6'-diamino-3,3'-methylenedibenzoic acid; then modifying graphene oxide with the modified diamine to obtain modified graphene oxide; and finally preparing modified polyimide by polycondensation reaction of 4,4'-diaminodiphenylmethane, modified graphene oxide, and 2,2'-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride.

[0004] However, in the above technical solutions, the synthesis of modified polyimide involves the use of various organic solvents and catalysts, and the reaction conditions of each step are quite different. Furthermore, the introduction of modified graphene oxide relies on chemical grafting, making it difficult to precisely control its dispersion uniformity in the polyimide matrix. This can easily lead to inconsistent thermal insulation performance in different areas of the composite coating, thereby affecting the overall fireproof and thermal insulation stability of the fabric.

[0005] Therefore, there is an urgent need for a method to prepare carbon fiber composite materials, which combines carbon fiber fabric with carbon aerogel in a laminated sandwich structure, so that the resulting material can simultaneously possess fireproof, heat insulation and infrared stealth functions, thereby meeting comprehensive protection requirements. Summary of the Invention

[0006] To address this, the present invention provides a method for preparing fire-resistant and heat-insulating carbon fiber and its application in fire-resistant and heat-insulating fabrics, thereby overcoming the problems in the prior art where key parameters in the carbon fiber material preparation process cannot be adjusted in real time, resulting in incomplete coordination polymer structure, uneven distribution of carbon aerogel pores, unstable heat insulation performance, and lack of infrared shielding function.

[0007] To achieve the above objectives, the present invention provides a method for preparing fire-resistant and heat-insulating carbon fiber, comprising: Polyacrylonitrile copolymer is dissolved in dimethylacetamide solution to obtain spinning slurry, and then spun and stretched to produce fiber filaments; The fiber filaments were placed in a gas mixture of oxygen and hydrogen bromide and pre-oxidized at a preset radiation temperature. The surface bromine content during the pre-oxidation process is detected, and based on the comparison with the preset bromine content, it is determined whether to adjust the preset radiation temperature to obtain pre-oxidized fibers. The breaking elongation of the pre-oxidized fiber was detected and the pre-oxidized fiber was spun based on a determined textile tension to form an initial fabric, and the surface roughness was determined. The dimethylacetamide solution, zinc chloride solution, and sodium hydroxide solution are mixed, and a coordination reaction is carried out at a preset coordination temperature. The zinc-sodium concentration ratio is determined based on the ratio of zinc ion concentration to sodium ion concentration during the coordination reaction, and the characteristic peak area ratio of the corresponding ions is determined based on the zinc-oxygen bond and the sodium-oxygen bond. The zinc chloride solution or the sodium hydroxide solution is added based on the zinc-sodium concentration ratio and the preset zinc-sodium concentration ratio, and the addition flow rate and addition method are determined based on the characteristic peak area ratio of the corresponding ions and the corresponding preset characteristic peak area ratio to obtain the bimetallic coordination polymer. The bimetallic coordination polymer was carbonized under a protective atmosphere to obtain a carbon aerogel, and the compression resilience was determined. The composite pressure and composite temperature are determined based on the surface roughness and the compression resilience, and the initial fabric and the carbon aerogel are laminated together to obtain a carbon fiber composite material.

[0008] Furthermore, the process of adding the zinc chloride solution or the sodium hydroxide solution includes: Based on the comparison results showing that the zinc-sodium concentration ratio is less than the lower limit of the preset zinc-sodium concentration ratio, it is determined that the zinc chloride solution should be added. Based on the comparison results showing that the zinc-sodium concentration ratio is greater than the upper limit of the preset zinc-sodium concentration ratio, it is determined that the sodium hydroxide solution should be added.

[0009] Furthermore, the process of determining the supplementary flow rate and the supplementary method includes: If it is determined that the zinc chloride solution will be added, the characteristic peak area ratio of the corresponding ions will be determined as the characteristic peak area ratio of zinc ions; Based on the comparison results of the zinc ion characteristic peak area ratio being less than or equal to the preset zinc ion characteristic peak area ratio, a proportional replenishment method and a first replenishment flow rate are determined, and the first replenishment flow rate is determined based on the difference in zinc ion characteristic peak area. Based on the comparison results showing that the zinc ion characteristic peak area ratio is greater than the preset zinc ion characteristic peak area ratio, a uniform replenishment method and a second replenishment flow rate are determined.

[0010] Furthermore, the process of determining the supplementary flow rate and the supplementary method also includes: If it is determined that the sodium hydroxide solution will be added, the characteristic peak area ratio of the corresponding ions will be determined to be the characteristic peak area ratio of sodium ions; Based on the comparison results of the sodium ion characteristic peak area ratio being less than or equal to the preset sodium ion characteristic peak area ratio, it is determined that a distributed replenishment method and a third replenishment flow rate will be adopted, and the third replenishment flow rate will be determined based on the sodium ion characteristic peak area difference. Based on the comparison results showing that the sodium ion characteristic peak area ratio is greater than the preset sodium ion characteristic peak area ratio, a uniform replenishment method and a fourth replenishment flow rate are determined.

[0011] Furthermore, the process of determining the composite pressure and composite temperature includes: The roughness difference is determined based on the absolute value of the difference between the surface roughness and the preset roughness, and the springback difference is determined based on the absolute value of the difference between the compression springback rate and the preset springback rate. The composite coefficient is calculated based on the roughness difference and the springback difference.

[0012] Furthermore, the process of determining the composite pressure and composite temperature also includes: The initial composite pressure and initial composite temperature are determined based on the textile tension. Based on the comparison results of the composite coefficient being less than the lower limit of the preset composite coefficient, it is determined to increase the initial composite pressure and the initial composite temperature, and the increase in the initial composite pressure and the initial composite temperature are both positively correlated with the composite offset value. Based on the comparison results of the composite coefficient being greater than the upper limit of the preset composite coefficient, it is determined to reduce the initial composite pressure and the initial composite temperature, and the reduction of the initial composite pressure and the initial composite temperature are both positively correlated with the composite difference.

[0013] Furthermore, the process of obtaining carbon aerogel includes: The dielectric constant of the bimetallic coordination polymer was detected at several time points during the carbonization process to obtain the rate of change of dielectric constant. Based on the fact that the rate of change of the dielectric constant is less than the lower limit of the preset rate of change, the heating rate in the carbonization process is increased, and the increase in the heating rate is positively correlated with the difference in the rate of change. Based on the fact that the rate of change of the dielectric constant is greater than the upper limit of the preset rate of change, the heating rate during the carbonization process is reduced, and the reduction in the heating rate is positively correlated with the offset value of the rate of change.

[0014] Furthermore, the process of determining whether to adjust the preset radiation temperature includes: Based on the comparison results of the surface bromine content being less than the lower limit of the preset bromine content, it is determined to increase the preset radiation temperature; Based on the comparison results of the surface bromine content being greater than the upper limit of the preset bromine content, it is determined to reduce the preset radiation temperature.

[0015] Furthermore, the preset radiation temperature is increased based on the comparison result between the bromine content difference and the preset bromine content difference, and the increase in the preset radiation temperature is positively correlated with the bromine content difference. The preset radiation temperature is reduced based on the comparison between the bromine content offset value and the preset bromine content offset value, and the reduction in the preset radiation temperature is positively correlated with the bromine content offset value.

[0016] The present invention also provides the application of fire-resistant and heat-insulating carbon fiber in fire-resistant and heat-insulating fabrics, wherein the fire-resistant and heat-insulating fabrics prepared based on the carbon fiber composite material have infrared signal shielding function.

[0017] Compared with the prior art, the beneficial effects of this invention are as follows: by dissolving polyacrylonitrile-based copolymers in dimethylacetamide to prepare spinning slurry, obtaining fiber precursors through spinning and stretching, and pre-oxidizing in a mixed gas containing oxygen and hydrogen bromide, the radiation temperature is dynamically adjusted based on the comparison between the surface bromine content and the preset bromine content. This overcomes the defects of traditional pre-oxidation methods, such as fixed pre-oxidation temperature and uncontrollable reaction degree, ensuring uniform transformation of the trapezoidal structure of the pre-oxidized fiber and stabilizing the surface bromine content within the target range. Furthermore, the textile tension is determined by detecting the breaking elongation of the pre-oxidized fiber, and the initial fabric is spun based on the negative correlation between tension and elongation, while simultaneously detecting the surface roughness of the fabric. This invention provides a matching basis for subsequent lamination and composite processes. By real-time monitoring of the zinc-sodium concentration ratio and characteristic peak area ratio during the coordination reaction, and dynamically adding zinc chloride or sodium hydroxide solution while controlling the addition flow rate and method, the stoichiometry and structural integrity of the bimetallic coordination polymer are ensured. By dynamically adjusting the heating rate based on the dielectric constant change rate during carbonization, the pore structure and compression resilience of the carbon aerogel are optimized. By calculating the composite coefficient based on surface roughness and compression resilience, and combining it with textile tension to determine the initial composite parameters, the pressure and temperature of the lamination and composite processes are dynamically adjusted, achieving a balance between interfacial bonding quality and aerogel structural protection. This invention uses the bromine content in the pre-oxidation stage, the elongation at break in the textile stage, the zinc-sodium concentration ratio and peak area ratio in the coordination stage, the dielectric constant change rate in the carbonization stage, and the surface roughness and compression resilience in the composite stage as the control basis for each process. This allows the output parameters of the previous process to directly determine the input benchmark of the next process, thereby significantly improving the fire resistance, heat insulation, infrared signal shielding function, and overall protective performance of the fire-resistant and heat-insulating carbon fiber composite material.

[0018] Furthermore, the present invention also avoids insufficient or excessive pre-oxidation caused by a single temperature decision by setting a dual judgment rule that increases the radiation temperature when the surface bromine content is below the lower limit and decreases the radiation temperature when it is above the upper limit, thereby forming a homogenized carbonized structure of the fiber structure and obtaining a carbon aerogel with stable compression resilience.

[0019] Furthermore, this invention introduces a graded control mechanism for bromine content difference and offset value, so that the adjustment range of radiation temperature matches the degree of deviation of bromine content, thereby achieving precise control of the pre-oxidation reaction from qualitative to quantitative, and effectively avoiding temperature overshoot or response lag.

[0020] Furthermore, this invention determines whether to add zinc chloride or sodium hydroxide solution by comparing the zinc-sodium concentration ratio with a preset concentration ratio. Based on the comparison of the characteristic peak area ratio of zinc or sodium ions with a preset value, proportional, uniform, or distributed addition methods and corresponding flow rates are adopted respectively. This achieves precise closed-loop control of the metal ion ratio in the coordination reaction, overcomes the deficiency of not being able to add solution in real time based on changes in ion concentration, and ensures the purity and yield of the bimetallic coordination polymer.

[0021] Furthermore, the present invention also dynamically increases or decreases the heating rate by comparing the change rate of dielectric constant during carbonization with the preset change rate, and determines the adjustment range based on the graded comparison of the difference in change rate with the preset difference, so as to avoid the collapse of the pore structure due to excessive heating or insufficient carbonization due to excessive heating during carbonization, thereby obtaining carbon aerogel with uniform structure and stable resilience.

[0022] Furthermore, the present invention also obtains the composite coefficient by weighting the difference between surface roughness and preset roughness, and the difference between compression resilience and preset resilience. Combined with the initial composite pressure and temperature determined by textile tension, the composite parameters are dynamically increased or decreased based on the comparison results between the composite coefficient and the preset composite coefficient range. This achieves a dynamic balance between the interfacial bonding strength and the protection of the aerogel structure during the lamination process, avoiding the aerogel crushing due to excessive pressure or the interface debonding due to insufficient pressure. Attached Figure Description

[0023] Figure 1 This is a system block diagram of the method for preparing fire-resistant and heat-insulating carbon fiber in an embodiment of the present invention; Figure 2 This is a schematic flowchart of the method for preparing fire-resistant and heat-insulating carbon fiber in an embodiment of the present invention; Figure 3 This is a flowchart illustrating the logic of adjusting the preset radiation temperature based on the comparison between the surface bromine content and the preset bromine content in an embodiment of the present invention. Figure 4 This is a morphology diagram of the nanoparticles of the bimetallic coordination polymer in an embodiment of the present invention; Figure 5 The image shows the infrared spectrum of the bimetallic coordination polymer in an embodiment of the present invention. Detailed Implementation

[0024] To make the objectives and advantages of the present invention clearer, the present invention will be further described below with reference to embodiments; it should be understood that the specific embodiments described herein are merely for explaining the present invention and are not intended to limit the present invention.

[0025] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0026] It should be noted that in the description of this invention, the terms "upper", "lower", "left", "right", "inner", "outer", etc., which indicate directions or positional relationships, are based on the directions or positional relationships shown in the accompanying drawings. This is only for the convenience of description and is not intended to indicate or imply that the device or element must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, it should not be construed as a limitation of this invention.

[0027] Furthermore, it should be noted that, in the description of this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0028] In this embodiment, the spinning slurry comprises, by mass percentage: 25%–35% polyacrylonitrile-based copolymer and 65%–75% dimethylacetamide; when preparing carbon aerogel, the molar ratio of zinc chloride, 2,5-furandicarboxylic acid, and sodium hydroxide is (0.8–1.2):(1.8–2.2):(1.8–2.2). A 0.08 mol / L aqueous solution of zinc chloride, a 0.08 mol / L dimethylacetamide solution of 2,5-furandicarboxylic acid, and a 0.16 mol / L aqueous solution of sodium hydroxide are prepared, and the corresponding volumes are mixed according to the above molar ratio to carry out a coordination reaction.

[0029] Please see Figure 1 As shown, it is a system block diagram of the method for preparing fire-resistant and heat-insulating carbon fiber in an embodiment of the present invention.

[0030] In this embodiment, the system includes a fiber preparation module, an aerogel preparation module, a lamination and composite module, and an intelligent control module.

[0031] The fiber preparation module is used to dissolve polyacrylonitrile-based copolymers in dimethylacetamide to prepare spinning slurry, which is then spun and stretched to obtain fiber filaments. The fiber filaments are then placed in a mixture of oxygen and hydrogen bromide and pre-oxidized at a preset radiation temperature to produce pre-oxidized fibers. The spinning tension is determined based on the breaking elongation, and the fibers are spun into an initial fabric. The surface roughness is also measured. This module includes a spinning unit, a pre-oxidation unit, and a spinning unit. The spinning unit dissolves the polyacrylonitrile-based copolymer in dimethylacetamide to prepare spinning slurry, which is then spun and stretched to obtain fiber filaments. The pre-oxidation unit, connected to the spinning unit, places the fiber filaments in a mixture of oxygen and hydrogen bromide and pre-oxidizes them at a preset radiation temperature. The radiation temperature is dynamically adjusted based on a comparison between the surface bromine content and a preset bromine content to obtain pre-oxidized fibers. The spinning unit, connected to the pre-oxidation unit, measures the breaking elongation of the pre-oxidized fibers, determines the spinning tension based on a comparison between the breaking elongation and a preset breaking elongation, and then spins the pre-oxidized fibers into an initial fabric, measuring the surface roughness.

[0032] The aerogel preparation module is connected to the fiber preparation module. It is used to mix a dimethylacetamide solution of 2,5-furandicarboxylic acid, a zinc chloride solution, and a sodium hydroxide solution to carry out a coordination reaction to obtain a bimetallic coordination polymer. This polymer is then carbonized to obtain a carbon aerogel, which includes a coordination reaction unit and a carbonization unit. The coordination reaction unit is used to mix the above solutions and carry out the coordination reaction at a preset coordination temperature. Based on the comparison between the zinc-sodium concentration ratio and the preset zinc-sodium concentration ratio, it determines whether to add zinc chloride or sodium hydroxide solution, and based on the comparison between the characteristic peak area ratio of zinc ions and sodium ions and the corresponding preset peak area ratio, it determines the addition flow rate and addition method to obtain the bimetallic coordination polymer. The carbonization unit, connected to the coordination reaction unit, is used to carbonize the bimetallic coordination polymer under a protective atmosphere. Based on the comparison between the dielectric constant change rate and the preset change rate, it dynamically adjusts the heating rate to obtain the carbon aerogel and detects the compression rebound rate.

[0033] The lamination module is connected to the aerogel preparation module. It is used to laminate the initial fabric with carbon aerogel to obtain carbon fiber composite material. It includes a lamination unit and a hot-pressing unit. The lamination unit is used to use carbon aerogel as the core layer, with the initial fabric covering the upper and lower surfaces to form a sandwich-type lamination structure. The hot-pressing unit is used to calculate the composite coefficient based on the weighted average of surface roughness and compression resilience. Based on the comparison result of the composite coefficient and the preset composite coefficient, the composite pressure and temperature are determined. Hot-pressing is performed at this pressure and temperature to obtain carbon fiber composite material.

[0034] The intelligent control module is connected to the fiber preparation module, aerogel preparation module, and lamination module, respectively. It is used to monitor key parameters of each process in real time and generate control commands. It includes a bromine content control unit, a tension control unit, a coordination control unit, a carbonization control unit, and a composite control unit. The bromine content control unit monitors the surface bromine content and dynamically adjusts the radiation temperature after comparing it with the preset bromine content. The tension control unit monitors the breaking elongation and determines the textile tension based on the comparison results. The coordination control unit monitors the zinc-sodium concentration ratio and the zinc ion characteristic peak area ratio to determine the replenishment flow rate and method of zinc chloride, and also monitors the sodium ion characteristic peak area ratio to determine the replenishment flow rate and method of sodium hydroxide solution. The carbonization control unit monitors the dielectric constant change rate to dynamically adjust the heating rate. The composite control unit monitors the surface roughness and compression resilience, calculates the composite coefficient by weighting, and determines the pressure and temperature for lamination.

[0035] Please see Figure 2 As shown, this is a schematic flowchart of the preparation method of fire-resistant and heat-insulating carbon fiber in an embodiment of the present invention. The control method in this embodiment includes at least the following steps: S1: Dissolve the polyacrylonitrile copolymer in a dimethylacetamide solution to obtain the spinning slurry; Specifically, a polyacrylonitrile copolymer is added to dimethylacetamide to achieve a polyacrylonitrile copolymer mass concentration of 25% to 35%, and then heated to 60 to 80°C and stirred continuously at a speed of 200 to 400 r / min for 4 to 6 hours to obtain a spinning slurry.

[0036] S2: Spinning and stretching the spinning slurry to produce fiber filaments; Specifically, a wet spinning method is used to spin and stretch the spinning slurry to produce polyacrylonitrile fiber precursor. In this embodiment, the spinning temperature can be set to 25-35°C, and the stretching ratio can be set to 3-8 times.

[0037] S3: The fiber filaments are placed in a mixed gas and pre-oxidized at a preset radiation temperature, wherein the mixed gas includes oxygen and hydrogen bromide; Specifically, polyacrylonitrile fiber precursors are placed in a mixed gas and pre-oxidized for 30 to 90 minutes at a preset radiation temperature to obtain pre-oxidized fibers. In this embodiment, the volume ratio of oxygen to hydrogen bromide in the mixed gas can be set to (10 to 20): 1; the preset radiation temperature can be set to 250°C.

[0038] S4: Detect the surface bromine content during the pre-oxidation process, and determine whether to adjust the preset radiation temperature to obtain pre-oxidized fibers based on the comparison with the preset bromine content; Please see Figure 3As shown, it is a logic flowchart of adjusting the preset radiation temperature based on the comparison result of the surface bromine content and the preset bromine content in an embodiment of the present invention.

[0039] Specifically, the surface bromine content B of the fiber is detected in real time during the pre-oxidation process, and a preset bromine content B0 is set in advance. The surface bromine content B is compared with the preset bromine content B0, and the preset radiation temperature is adjusted based on the comparison result.

[0040] In this embodiment, the preset bromine content B0 is established based on the baseline data of fiber surface bromine content under a standard pre-oxidation process. Specifically, under the premise of stable pre-oxidation temperature, mixed gas ratio, and fiber speed, standard process data that has been rigorously confirmed to be uniform in pre-oxidation degree and good in fiber structure transformation are collected. By collecting multiple sets of surface bromine content data, a standard baseline sample set is constructed. The normal fluctuation range of the sample set is calculated to determine the lower limit value Bi and the upper limit value Ba of the surface bromine content, which are used as the preset bromine content range. For example, the preset bromine content B0 can be set to [0.5%, 2.5%]. The process of comparing the surface bromine content B with the preset bromine content B0 is as follows: If B is less than Bi, it indicates that the pre-oxidation reaction is insufficient and the bromine content on the fiber surface is too low. Therefore, it is determined to increase the preset radiation temperature to promote the bromination reaction process, accelerate the formation of cyclization structure, and avoid fiber structure defects caused by insufficient pre-oxidation.

[0041] The difference between the preset lower limit value Bi of bromine content and the surface bromine content B is calculated and denoted as the bromine content difference ΔBX. The preset bromine content difference ΔBX0 includes a first preset bromine content difference ΔBX1 and a second preset bromine content difference ΔBX2, and ΔBX1 is exemplarily set to 0.1% and ΔBX2 to 0.2%. The increase in preset radiation temperature is determined based on the comparison between the bromine content difference ΔBX and ΔBX1 and ΔBX2. As the bromine content difference ΔBX increases, it indicates a more severe degree of insufficient pre-oxidation reaction, requiring a greater temperature increase to accelerate the bromination reaction and cyclization process. Therefore, the increase in preset radiation temperature increases with the increase of the bromine content difference ΔBX. If ΔBX is less than or equal to ΔBX1, the preset radiation temperature is increased to 1.05 times its initial value based on the generated first preset radiation temperature increase command; where, if the preset radiation temperature is 250℃, the increased preset radiation temperature is 262.5℃. If ΔBX is greater than ΔBX1 and less than or equal to ΔBX2, the preset radiation temperature is increased to 1.15 times its initial value based on the generated second preset radiation temperature increase command. If ΔBX is greater than ΔBX2, the preset radiation temperature is increased to 1.2 times its initial value based on the generated third preset radiation temperature increase command. The increased preset radiation temperature must not exceed the safe upper limit temperature of the pre-oxidation process, which can be exemplarily set at 300℃.

[0042] If B∈B0, it indicates that the pre-oxidation reaction is suitable and the surface bromine content is within the normal fluctuation range. Therefore, it is determined to maintain the preset radiation temperature to keep the current reaction conditions stable and avoid unnecessary temperature fluctuations.

[0043] If B is greater than Ba, it indicates that the pre-oxidation reaction is excessive and the bromine content on the fiber surface is too high. Therefore, it is determined to reduce the preset radiation temperature to inhibit the bromination reaction from proceeding too quickly and avoid excessive carbonization or structural embrittlement of the fiber surface.

[0044] The difference between the surface bromine content B and the upper limit of the preset bromine content Ba is calculated and recorded as the bromine content offset value ΔBP. The preset bromine content offset value ΔBP0 includes a first preset bromine content offset value ΔBP1 and a second preset bromine content offset value ΔBP2, and ΔBP1 is exemplarily set to 0.15% and ΔBP2 to 0.25%. The reduction range of the preset radiation temperature is determined based on the comparison between the bromine content offset value ΔBP and ΔBP1 and ΔBP2. As the bromine content offset value ΔBP increases, it indicates a more severe degree of over-oxidation reaction, requiring a greater cooling to suppress over-oxidation. Therefore, the reduction range of the preset radiation temperature increases with the increase of the bromine content offset value ΔBP. If ΔBP is less than or equal to ΔBP1, the preset radiation temperature is reduced to 0.95 times its initial value based on the generated first preset radiation temperature reduction command. For example, if the preset radiation temperature is 250℃, the reduced preset radiation temperature will be 237.5℃. If ΔBP is greater than ΔBP1 and less than or equal to ΔBP2, the preset radiation temperature is reduced to 0.9 times its initial value based on the generated second preset radiation temperature reduction command. If ΔBP is greater than ΔBP2, the preset radiation temperature is reduced to 0.85 times its initial value based on the generated third preset radiation temperature reduction command. The reduced preset radiation temperature must not exceed the safe lower limit temperature of the pre-oxidation process, which can be exemplarily set at 200℃. It should be noted that increasing or decreasing the preset radiation temperature will not negatively affect the preparation process of the pre-oxidized fiber.

[0045] S5: Detect the breaking elongation of the pre-oxidized fiber and spin the pre-oxidized fiber based on the determined textile tension to make an initial fabric, and detect the surface roughness of the initial fabric. Specifically, the breaking elongation of the pre-oxidized fiber was tested. To ensure the accuracy of the breaking elongation data, each sample was tested 10 times, and the arithmetic mean was taken as the breaking elongation E. A preset breaking elongation E0 was set in advance, and the textile tension F was determined based on the comparison results. The preset breaking elongation E0 can be divided into a first preset breaking elongation E01 and a second preset breaking elongation E02.

[0046] In this embodiment, the preset elongation at break E0 is established based on the baseline mechanical property data of pre-oxidized fibers under a standard pre-oxidation process. Specifically, under the premise of stable pre-oxidation temperature, mixed gas ratio, and fiber travel speed, standard pre-oxidized fiber samples with uniform pre-oxidation degree and good fiber structure transformation are collected. Multiple sets of elongation at break data are collected using a single fiber tensile tester to form a standard baseline sample set. The lower limit value or a specific low quantile (such as the 5th percentile) of the sample set is calculated to establish the preset elongation at break E0. For example, E01 = 12% and E02 = 18%.

[0047] If E is less than or equal to E01, the textile tension F is determined to be 1.2 cN / dtex; if E is greater than E01 and less than or equal to E02, the textile tension F is determined to be 1.0 cN / dtex; if E is greater than E02, the textile tension F is determined to be 0.8 cN / dtex. The textile tension F decreases as the breaking elongation E increases. When the breaking elongation E is small, it indicates a high degree of cyclization in the pre-oxidized fiber, resulting in increased fiber rigidity and brittleness. During spinning, the cohesion between fibers is poor, and monofilaments are prone to scattering and pilling. Therefore, a larger textile tension is needed to enhance the bundle's cohesion and compactness during drafting, preventing fiber breakage due to insufficient cohesion. When the breaking elongation E is large, it indicates good fiber flexibility and strong cohesion. Excessive tension can lead to overstretching or even breakage of the fiber; therefore, the tension should be appropriately reduced to avoid damage.

[0048] Based on the textile tension F, pre-oxidized fibers are spun into yarn, which is then woven into initial fabric. A surface profilometer is used to measure the surface roughness M at 10 randomly selected points on the fabric surface. The arithmetic mean of all points is taken as the surface roughness M of the initial fabric. To ensure data representativeness, each point is measured three times, and the average value of each point is then used in the overall arithmetic mean calculation.

[0049] S6: Mix dimethylacetamide solution, zinc chloride solution and sodium hydroxide solution, and carry out the coordination reaction according to the preset coordination temperature; Specifically, a dimethylacetamide solution of 2,5-furandicarboxylic acid, a zinc chloride solution, and a sodium hydroxide solution are mixed to obtain a mixture. The mixture is then subjected to a coordination reaction at a preset coordination temperature. In this embodiment, the preset coordination temperature can be exemplarily set to 120°C.

[0050] S7: Detect the zinc ion concentration, sodium ion concentration, zinc-oxygen bond, and sodium-oxygen bond during the coordination reaction process, and determine the zinc-sodium concentration ratio based on the ratio of zinc ion concentration to sodium ion concentration, and determine the characteristic peak area ratio of the corresponding ions based on the zinc-oxygen bond and sodium-oxygen bond. Specifically, samples are taken every 30 minutes to measure the zinc ion concentration (CZn) and sodium ion concentration (CNa) in the reaction solution. The zinc-to-sodium concentration ratio (R) is calculated, where R = CZn / CNa.

[0051] Furthermore, infrared spectra of the reaction solution samples were collected, with a scanning range of 4000–400 cm⁻¹. -1 4 cm resolution -1 In the infrared spectrum, the characteristic absorption peak of the zinc-oxygen bond is located at 450–550 cm⁻¹. -1 The characteristic absorption peak of the sodium-oxygen bond is located at 350–450 cm⁻¹. -1 The peak areas A1 and A2 of the zinc-oxygen bond characteristic peaks were calculated using the integral method. The ratio P of the zinc ion characteristic peak area was calculated based on the peak areas A1 and A2 of the sodium-oxygen bond characteristic peaks, with the calculation process being P = A1 / A2. Similarly, the ratio Q of the sodium ion characteristic peak area was calculated based on the peak areas A2 and A1 of the sodium-oxygen bond characteristic peaks, with the calculation process being Q = A2 / A1.

[0052] S8: Determine whether to add zinc chloride solution or sodium hydroxide solution based on the comparison result of zinc-sodium concentration ratio and preset zinc-sodium concentration ratio, and determine the addition flow rate and addition method based on the comparison result of characteristic peak area ratio of corresponding ions and corresponding preset characteristic peak area ratio to obtain bimetallic coordination polymer. Specifically, by setting a preset zinc-sodium concentration ratio R0, the zinc-sodium concentration R is compared with the preset zinc-sodium concentration ratio R0, and then the comparison result is used to determine whether to add zinc chloride solution or sodium hydroxide solution.

[0053] In this embodiment, the preset zinc-sodium concentration ratio R0 is established based on the theoretical stoichiometry of the target product [ZnNa2(FDA)2] and background fluctuation data under standard coordination reaction conditions. Specifically, the theoretical zinc-sodium concentration ratio R = CZn / CNa = 0.5 is calculated based on the theoretical stoichiometry of zinc ions to sodium ions in the product (Zn:Na = 1:2). Under stable reaction temperature, raw material concentration, and stirring rate, standard coordination reaction data with strictly confirmed complete reaction and good product structure are collected. Multiple sets of steady-state zinc-sodium concentration ratio data are collected to form a standard background sample set. The normal fluctuation range of the sample set is calculated, and the lower limit Ri and upper limit Ra of the zinc-sodium concentration ratio are determined as the preset zinc-sodium concentration ratio R0. For example, R0 = [0.4, 0.6]. The process of comparing the zinc-sodium concentration ratio R with the preset zinc-sodium concentration ratio R0 is as follows: If R is less than Ri, it indicates that there is a relative deficiency of zinc ions in the reaction system. Therefore, it is determined to add zinc chloride solution to avoid the loss of coordination sites and incomplete [ZnNa2(FDA)2] skeleton structure due to insufficient zinc ions.

[0054] Furthermore, when determining the addition of zinc chloride solution, the zinc ion characteristic peak area ratio P is compared with the preset zinc ion characteristic peak area ratio P0, and then the addition flow rate and addition method are determined based on the comparison results.

[0055] In this embodiment, the preset zinc ion characteristic peak area ratio P0 is established based on the background data of the zinc ion coordination state under the standard coordination reaction conditions of the target product [ZnNa2(FDA)2]. Specifically, under the premise of stable reaction temperature, raw material concentration, and stirring rate, standard coordination reaction data that has been rigorously confirmed to be complete and with a well-structured product are collected. Multiple sets of steady-state zinc ion characteristic peak area ratio data are collected to form a standard background sample set. The upper limit or a specific high quantile (e.g., the 95th percentile) of the sample set is calculated to establish the preset zinc ion characteristic peak area ratio P0. For example, P0 = 1.2 can be set. The process of comparing the zinc ion characteristic peak area ratio P with the preset zinc ion characteristic peak area ratio P0 is as follows: If P is less than or equal to P0, it indicates that the coordination degree of zinc ions is insufficient or the activity of zinc ions in the reaction system is low. The degree of insufficiency increases as P decreases. Therefore, a proportional addition method and a first addition flow rate are determined to ensure complete coordination reaction, intact product structure and accurate stoichiometry.

[0056] In this embodiment, the difference between the preset zinc ion characteristic peak area ratio P0 and the zinc ion characteristic peak area ratio P is denoted as the zinc ion characteristic peak area difference ΔP1. The ratio of ΔP1 to P0 is denoted as the first replenishment flow rate coefficient k1. The first replenishment flow rate L1 is determined by multiplying the first replenishment flow rate coefficient k1 with the initial addition amount of zinc chloride solution LZn. Wherein, ΔP1=P0-P, k1=ΔP1 / P0, L1=k1×LZn; the proportional replenishment method is such that the first replenishment flow rate L1 and the difference in characteristic peak area ratio ΔP1 are positively correlated; the initial addition amount of zinc chloride solution LZn can be exemplarily set to 5L / h.

[0057] If P is greater than P0, it indicates that the zinc ion coordination is good or the zinc ion in the reaction system is close to saturation, requiring only maintenance replenishment. Therefore, a uniform replenishment method and a second replenishment flow rate are determined to continuously replenish zinc chloride solution at a constant rate, offsetting the reaction consumption or flow loss of zinc ions and maintaining a stable zinc ion concentration. In this embodiment, the difference between the zinc ion characteristic peak area ratio P and the preset zinc ion characteristic peak area ratio P0 is recorded as the zinc ion characteristic peak area offset value ΔP2. The ratio of ΔP2 to P0 is recorded as the second replenishment flow rate coefficient k2. The second replenishment flow rate L2 is determined by multiplying the second replenishment flow rate coefficient k2 with the initial amount of zinc chloride solution added LZn. The calculation process is L2 = k2 × LZn + Lb1. Wherein, ΔP2=P-P0, k2=ΔP2 / P0, and Lb1 is the steady-state replenishment flow rate of zinc chloride, which is used to offset the steady-state consumption of zinc ions. For example, Lb1 can be set to 20% of the initial amount of zinc chloride solution added, LZn, i.e., Lb1=20%×LZn.

[0058] If R∈R0, it indicates that the zinc-sodium concentration ratio is within the normal fluctuation range and meets the theoretical stoichiometric ratio requirement. Therefore, it is determined to maintain the current operation and not add any more sodium, thereby keeping the reaction system stable.

[0059] If R is greater than Ra, it indicates that there is a relative deficiency of sodium ions in the reaction system. Therefore, it is determined to add sodium hydroxide solution to avoid the loose crystal structure and reduced porosity of [ZnNa2(FDA)2] due to insufficient sodium ions.

[0060] Furthermore, when determining the addition of sodium hydroxide solution, the sodium ion characteristic peak area ratio Q is compared with the preset sodium ion characteristic peak area ratio Q0, and then the addition flow rate and addition method are determined based on the comparison results.

[0061] In this embodiment, the preset sodium ion characteristic peak area ratio Q0 is established based on the background data of sodium ion coordination state under standard coordination reaction conditions of the target product [ZnNa2(FDA)2]. Specifically, under stable reaction temperature, raw material concentration, and stirring rate, standard coordination reaction data with strictly confirmed complete reaction and good product structure are collected. Multiple sets of steady-state sodium ion characteristic peak area ratio data are collected to form a standard background sample set. The upper limit or a specific high quantile (e.g., the 95th percentile) of the sample set is calculated to establish the preset sodium ion characteristic peak area ratio Q0, which can be set to Q0=0.83 for example. The process of comparing the sodium ion characteristic peak area ratio Q with the preset sodium ion characteristic peak area ratio Q0 is as follows: If Q is less than or equal to Q0, it indicates that the sodium ion coordination degree is insufficient or the sodium ion activity in the reaction system is low. The degree of insufficiency increases as Q decreases. Therefore, a distributed replenishment method and a third replenishment flow rate are adopted to divide the total replenishment into multiple portions and add them step by step at multiple time points or locations. This enhances the dispersion uniformity of sodium hydroxide solution in the reaction system, avoids excessively high or low local concentrations, ensures that sodium ions participate uniformly in the coordination reaction, and obtains structurally uniform [ZnNa2(FDA)2].

[0062] In this embodiment, the difference between the preset sodium ion characteristic peak area ratio Q0 and the sodium ion characteristic peak area ratio Q is denoted as the sodium ion characteristic peak area difference ΔQ1. The ratio of ΔQ1 to Q0 is denoted as the third replenishment flow rate coefficient. The third replenishment flow rate L3 is determined by multiplying the third replenishment flow rate coefficient k3 with the initial addition amount LNa of sodium hydroxide solution. Wherein, ΔQ1=Q0-Q, k3=ΔQ1 / Q0, L3=k3×LNa. In this embodiment, the initial addition amount LNa of sodium hydroxide solution can be set to 4L / h for example. The replenishment is performed in stages based on a preset time interval Δt, and the calculation process for each replenishment volume Lc is Lc=k3×LNa×Δt. In this embodiment, Δt can be set to 15min for example. The third replenishment flow rate is discretized into equal-volume stages with a period of Δt to achieve distributed replenishment and enhance the dispersion uniformity of the replenished substance in the reaction system.

[0063] If Q is greater than Q0, it indicates that the sodium ion coordination is good or the sodium ion concentration in the reaction system is close to saturation, requiring only maintenance replenishment. Therefore, a uniform replenishment method and a fourth replenishment flow rate are adopted to continuously replenish sodium hydroxide solution at a constant rate, offsetting reaction consumption or flow loss, maintaining a stable sodium ion concentration, and avoiding the impact of concentration fluctuations on the coordination reaction equilibrium. In this embodiment, the difference between the sodium ion characteristic peak area ratio Q and the preset sodium ion characteristic peak area ratio Q0 is recorded as the sodium ion characteristic peak area offset value ΔQ2. The ratio of ΔQ2 to Q0 is recorded as the fourth replenishment flow rate coefficient k4. The fourth replenishment flow rate L4 is determined by multiplying the fourth replenishment flow rate coefficient k4 with the initial amount of sodium hydroxide solution added LNa. The calculation process is L4 = k4 × LNa + Lb2. Wherein, ΔQ2=Q-Q0, k4=ΔQ2 / Q0, and Lb2 is the steady-state replenishment flow rate of sodium hydroxide, which is used to offset the steady-state consumption of sodium ions. For example, Lb2 can be set to 25% of the initial amount of sodium hydroxide solution added, LNa, i.e., Lb2=25%×LNa.

[0064] After the reaction was completed, the mixture was filtered to obtain a precipitate, which was washed 2 to 3 times with ethanol and dried at 60 to 80 °C to obtain the bimetallic coordination polymer [ZnNa2(FDA)2].

[0065] Please refer to the following documents separately. Figure 4 and Figure 5 As shown, Figure 4 The image shows the nanoparticle morphology of the bimetallic coordination polymer in an embodiment of the present invention. Figure 5 The image shows the infrared spectrum of the bimetallic coordination polymer in an embodiment of the present invention.

[0066] Figure 4 The morphology of the obtained product was characterized by scanning electron microscopy, and the scale bar was set to 200 nm to generate the morphology image of the bimetallic coordination polymer nanoparticles. The morphology image showed that the product had a short rod-shaped and elliptical morphology, with a relatively uniform particle size distribution, good dispersion between particles, a small amount of contact and stacking, but no severe hard agglomeration. This morphological feature is conducive to the subsequent carbonization to form a uniform carbon aerogel.

[0067] Figure 5 This is used to characterize the response of a sample to infrared light of different wavenumbers, thereby analyzing its functional group composition, chemical bond type, and coordination environment. The horizontal axis represents the wavenumber, reflecting the vibrational energy level corresponding to infrared absorption; the vertical axis represents the transmittance, reflecting the percentage of infrared light transmitted by the sample.

[0068] Based on Fourier transform infrared (FTIR) spectroscopy data, the matching of the bimetallic coordination polymer [ZnNa2(FDA)2] can be confirmed. Firstly, at 3400 cm⁻¹... -1The absorption peaks are typically attributed to the stretching vibrations of OH (hydroxyl) or NH (amino), indicating that the bimetallic coordination polymer contains amino or hydroxyl functional groups, consistent with the characteristics of organic ligands. Secondly, the 1700 cm⁻¹... -1 The absorption peak matches the C=O (carbonyl) stretching vibration, indicating that the bimetallic coordination polymer contains carboxylic acid or ester groups. (1400 cm⁻¹) -1 The absorption peak originates from the bending vibration of the CH (carbon-hydrogen single bond), indicating that the bimetallic coordination polymer contains hydrocarbon chains. Finally, the absorption peak is less than or equal to 1000 cm⁻¹. -1 The absorption peaks are correlated with the vibrations of functional groups such as CO (alcohol or ether) or CN (amine), representing other functional groups present in [ZnNa2(FDA)2]. Therefore, the FTIR spectrum of the bimetallic coordination polymer is consistent with that of [ZnNa2(FDA)2] and contains typical organic ligand structural features.

[0069] S9: Carbonize the bimetallic coordination polymer under a protective atmosphere to obtain carbon aerogel, and test the compression resilience of the carbon aerogel. Specifically, the dried [ZnNa2(FDA)2] is placed in a tube furnace, a protective atmosphere is introduced, and it is heated to a carbonization temperature of 800–1000°C at a heating rate of 10°C / min, and held at this temperature for 3–4 hours. After carbonization, it is allowed to cool naturally to room temperature in the furnace to obtain carbon aerogel. In this embodiment, nitrogen can be used as the protective atmosphere, with a nitrogen flow rate of 150 mL / min.

[0070] Furthermore, during the carbonization process of the bimetallic coordination polymer, the dielectric constant of the material in the furnace was measured at several time points, with a sampling frequency of 1 time / min. The rate of change of dielectric constant Δε within each 5-min interval was calculated as follows: Δε = (εt2 - εt1) / (t2 - t1). Here, εt1 is the dielectric constant value detected at time t1, εt2 is the dielectric constant value detected at time t2, t1 is the first detection time point, and t2 is the second detection time point.

[0071] In this embodiment, the preset change rate Δε0 is established based on the background data of the dielectric property changes of bimetallic coordination polymers under a standard carbonization process. Specifically, under the premise of stable carbonization temperature, heating rate, and protective atmosphere, standard carbonization process data that has been rigorously confirmed to show uniform reaction and good carbon aerogel structure transformation are collected. By collecting multiple sets of dielectric constant change rate data, a standard background sample set is constructed. The normal fluctuation range of the sample set is calculated, and the lower limit value Δεi and upper limit value Δεa of the dielectric constant change rate are determined as the preset change rate Δε0. For example, Δε0 = [5, 15] min can be set. -1 The process of comparing the rate of change of dielectric constant Δε with the preset rate of change Δε0 is as follows: If Δε is less than Δεi, it indicates that the carbonization reaction rate is low, the dielectric properties change slowly, and the carbonization conversion is insufficient. Therefore, it is determined to increase the heating rate during the carbonization process to accelerate the carbonization reaction and promote the structural transformation of the bimetallic coordination polymer into carbon aerogel.

[0072] The difference between the lower limit of the preset rate of change Δεi and the rate of change of the dielectric constant Δε is calculated and denoted as the rate of change difference ΔYX. The preset rate of change difference ΔYX0 includes the first preset rate of change difference ΔYX1 and the second preset rate of change difference ΔYX2, and ΔYX1 is set to 1.5 min for example. -1 ΔYX2=3min -1 The increase in heating rate is determined by comparing the rate difference ΔYX with ΔYX1 and ΔYX2. As the rate difference ΔYX increases, it indicates a more severe underestimation of the carbonization reaction rate, requiring a greater increase in heating rate to accelerate the reaction. Therefore, the increase in heating rate increases with the increase in the rate difference ΔYX. If ΔYX is less than or equal to ΔYX1, the heating rate is increased to 1.2 times the initial value based on the generated first heating rate increase command. Specifically, if the heating rate is 10℃ / min, it is increased to 12℃ / min. If ΔYX is greater than ΔYX1 and less than or equal to ΔYX2, the heating rate is increased to 1.3 times the initial value based on the generated second heating rate increase command. If ΔYX is greater than ΔYX2, the heating rate is increased to 1.4 times the initial value based on the generated third heating rate increase command.

[0073] If Δε∈Δε0, it indicates that the carbonization reaction rate is appropriate and the change in dielectric properties is within the normal fluctuation range. Therefore, it is determined to maintain the current heating rate in the carbonization process to keep the carbonization reaction stable.

[0074] If Δε is greater than Δεa, it indicates that the carbonization reaction is too intense and the dielectric properties change too quickly, which may cause defects in the carbon aerogel structure. Therefore, it is necessary to reduce the heating rate during the carbonization process to suppress the carbonization reaction from proceeding too quickly, and avoid defects such as pore structure collapse and skeleton rupture caused by local overheating or uncontrolled reaction rate, so as to ensure the integrity of the carbon aerogel structure and uniform pores.

[0075] The difference between the rate of change of dielectric constant Δε and the upper limit of the preset rate of change Δεa is calculated and recorded as the rate of change offset value ΔYZ. The preset rate of change offset value ΔYZ0 includes a first preset rate of change offset value ΔYZ1 and a second preset rate of change offset value ΔYZ2, and ΔYZ1 is set to 2min for example. -1 ΔYZ2=5min -1The decrease in heating rate is determined by comparing the rate of change offset value ΔYZ with ΔYZ1 and ΔYZ2. As the rate of change offset value ΔYZ increases, it indicates a more severe carbonization reaction, resulting in rapid changes in dielectric properties and a higher likelihood of defects in the carbon aerogel structure. Therefore, the decrease in heating rate increases with the increase of the rate of change offset value ΔYZ. If ΔYZ is less than or equal to ΔYZ1, the heating rate is reduced to 0.9 times the initial value based on the generated first heating rate reduction command. Specifically, if the initial heating rate is 10℃ / min, the reduced heating rate is 9℃ / min. If ΔYZ is greater than ΔYZ1 and less than or equal to ΔYZ2, the heating rate is reduced to 0.8 times the initial value based on the generated second heating rate reduction command. If ΔYZ is greater than ΔYZ2, the heating rate is reduced to 0.7 times the initial value based on the generated third heating rate reduction command. It should be noted that increasing or decreasing the heating rate will not negatively affect the preparation process of the carbon aerogel.

[0076] Carbon aerogel was processed into cylindrical specimens with a diameter of 10 mm and a height of 5 mm. These specimens were compressed to 50% of their original height at a compression rate of 1 mm / min, held for 30 seconds, and then unloaded. The height h2 of the specimen after unloading was measured, and the compression rebound rate h of a single test was calculated as h = (h2 / h1) × 100%. Here, h1 is the initial height of the specimen. Each sample was tested three times, and the arithmetic mean was taken as the compression rebound rate H of that batch of carbon aerogel.

[0077] S10: Determine the composite pressure and composite temperature based on surface roughness and compression resilience; Specifically, based on the comparison between the textile tension F and the preset textile tension F0, the initial composite pressure S0 and the initial composite temperature T0 are determined. The preset textile tension F0 can be divided into the first preset textile tension F01 and the second preset textile tension F02.

[0078] In this embodiment, the preset textile tension F0 is established based on baseline data of the mechanical properties and spinning stability of pre-oxidized fibers under standard textile processes. Specifically, under the premise of stable pre-oxidation process and fiber breaking elongation within the normal range (10%–25%), standard textile process data that has been rigorously confirmed to ensure stable spinning process operation and good yarn quality are collected. Multiple sets of textile tension data are collected to form a standard baseline sample set. The normal fluctuation range of the sample set is calculated, and the lower limit Fi and upper limit Fa of the textile tension are determined as the preset textile tension F0. For example, F01 = 0.8 cN / dtex and F02 = 1.2 cN / dtex are set.

[0079] If F is less than or equal to F01, the initial composite pressure S0 is set at 0.8 MPa and the initial composite temperature T0 at 130℃; if F is greater than F01 and less than F02, the initial composite pressure S0 is set at 1.0 MPa and the initial composite temperature T0 at 120℃; if F is greater than or equal to F02, the initial composite pressure S0 is set at 1.2 MPa and the initial composite temperature T0 at 110℃. The larger F is, the denser the fabric, requiring greater pressure for bonding. Simultaneously, the temperature can be appropriately lowered to avoid deformation caused by the release of internal stress.

[0080] Furthermore, in this embodiment, the preset roughness M0 is established based on the baseline data of the initial fabric surface roughness under the standard pre-oxidized fiber textile process. Specifically, under the premise of stable textile process parameters and fiber breaking elongation within the normal range (10%–25%), standard initial fabric samples with strictly confirmed good textile quality and uniform fabric surface are collected. Multiple sets of surface roughness data are acquired using a three-dimensional optical profilometer to form a standard baseline sample set. The normal fluctuation range of the sample set is calculated to determine the standard value of the surface roughness; for example, the preset roughness M0 can be set to 1.5 μm.

[0081] The preset rebound rate H0 is established based on the baseline data of the compression rebound performance of carbon aerogel under a standard carbonization process. Specifically, under stable carbonization temperature, heating rate, and protective atmosphere, standard carbon aerogel samples with thoroughly verified complete carbonization and good aerogel structure are collected. Multiple sets of compression rebound rate data are acquired using a universal testing machine to form a standard baseline sample set. The normal fluctuation range of the sample set is calculated to determine the standard value of the compression rebound rate. For example, the preset rebound rate H0 can be set to 90%.

[0082] The surface roughness difference ΔM is obtained by calculating the absolute value of the difference between surface roughness M and preset roughness M0, and the springback difference ΔH is obtained by calculating the absolute value of the difference between compression springback rate H and preset springback rate H0.

[0083] The roughness difference ΔM and the springback difference ΔH are normalized to eliminate the influence of dimensions, resulting in normalized roughness difference ΔM1 and normalized springback difference ΔH1. A composite coefficient X is then calculated based on a weighted average: X = α × ΔM1 + β × ΔH1. In this embodiment, the normalization processes for the roughness difference ΔM and springback difference ΔH are ΔM1 = ΔM / M0 and ΔH1 = ΔH / H0, respectively.

[0084] Wherein, α + β = 1. In this embodiment, the values ​​of α and β are determined as follows: Specifically, with other composite process parameters fixed, one set of samples with different values ​​of M and H are prepared, and the interfacial peel strength of each set of samples is measured. Using M and H0 as benchmarks, ΔM1 and ΔH1 of each set of samples are calculated. Linear regression analysis is used to analyze the relationship between peel strength and ΔM1 and ΔH1, revealing that the absolute value of the regression coefficient of peel strength on ΔH1 is approximately 1.5 times the absolute value of the regression coefficient on ΔM1. Therefore, α:β can be set to 1:1.5, i.e., α = 0.4 and β = 0.6, so that the response of the composite coefficient X to the degree of deviation of the two values ​​matches their actual influence on the interfacial peel strength.

[0085] Furthermore, by pre-setting a preset composite coefficient X0, the composite coefficient X is compared with the preset composite coefficient X0, and the composite pressure and composite temperature are determined based on the comparison results.

[0086] In this embodiment, the preset composite coefficient X0 is established based on baseline data of the initial fabric and carbon aerogel compatibility under a standard lamination process. Specifically, under the premise of stable lamination pressure, temperature, and batch-to-batch material conditions, process data is collected that has been rigorously confirmed to indicate good interfacial bonding, intact carbon aerogel structure, and satisfactory overall mechanical properties after lamination. Multiple sets of composite coefficient K values ​​are collected to form a standard baseline sample set. The normal fluctuation range of the sample set is calculated to determine the lower limit Xi and upper limit Xa of the composite coefficient, which are used as the preset composite coefficient X0. For example, X0 can be set to [0.5, 1.5]. The process of comparing the composite coefficient X with the preset composite coefficient X0 is as follows: If X is less than Xi, it indicates that the initial fabric and carbon aerogel have poor compatibility and insufficient interfacial bonding. Therefore, it is determined to increase the initial composite pressure and initial composite temperature to enhance the interfacial bonding strength between the initial fabric and carbon aerogel, and avoid defects such as interfacial peeling and delamination caused by insufficient pressure or temperature.

[0087] The difference between the lower limit value Xi and the composite coefficient X in the preset composite coefficient is calculated and recorded as the composite offset value ΔXZ. The preset composite difference ΔXZ0 includes the first preset composite difference ΔXZ1 and the second preset composite difference ΔXZ2, and ΔXZ1 is set to 0.13 and ΔXZ2 to 0.2, respectively. Based on the comparison of the composite difference ΔXZ with ΔXZ1 and ΔXZ2, the increase in the initial composite pressure and initial composite temperature is determined. As the composite difference ΔXZ increases, it indicates a worse match between the initial fabric and the carbon aerogel, and a more severe degree of insufficient interfacial bonding. Therefore, the increase in the initial composite pressure and initial composite temperature both increase with the increase in the composite difference ΔXZ. If ΔXZ is less than or equal to ΔXZ1, the initial composite pressure is increased to 1.05 times its initial value based on the generated first initial composite pressure increase command, and the initial composite temperature is increased to 1.08 times its initial value based on the generated first initial composite temperature increase command. Specifically, if the initial composite pressure is 0.8 MPa, the increased and adjusted initial composite pressure is 0.84 MPa; if the initial composite temperature is 130°C, the increased and adjusted initial composite temperature is 140.4°C. If ΔXZ is greater than ΔXZ1 and less than or equal to ΔXZ2, the initial composite pressure is increased to 1.15 times its initial value based on the generated second initial composite pressure increase command, and the initial composite temperature is increased to 1.18 times its initial value based on the generated second initial composite temperature increase command. If ΔXZ is greater than ΔXZ2, the initial composite pressure is increased to 1.25 times its initial value based on the generated third initial composite pressure increase command, and the initial composite temperature is increased to 1.28 times its initial value based on the generated third initial composite temperature increase command.

[0088] If X∈X0, it indicates that the initial fabric and carbon aerogel have good compatibility and are in a suitable composite range. Therefore, it is determined to maintain the initial composite pressure and initial composite temperature so that the initial fabric and carbon aerogel form a uniform and firm composite interface under suitable process parameters, ensuring the overall structural integrity and performance consistency of the composite material.

[0089] If X is greater than Xa, it indicates that the current composite conditions are too severe, which may cause the carbon aerogel structure to collapse or the fabric to deform. Therefore, it is necessary to reduce the initial composite pressure and initial composite temperature to avoid the collapse of the carbon aerogel pore structure, skeleton rupture or fabric thermal deformation caused by excessive composite pressure or temperature, and to protect the integrity of the porous structure of the carbon aerogel.

[0090] The difference between the composite coefficient X and the upper limit value Xa of the preset composite coefficient is calculated and denoted as the composite difference ΔXY. The preset composite offset value ΔXY0 includes the first preset composite offset value ΔXY1 and the second preset composite offset value ΔXY2, and ΔXY1 is set to 0.3 and ΔXY2 to 0.5, respectively. Based on the comparison between the composite difference ΔXY and ΔXY1 and ΔXY2, the reduction range corresponding to the initial composite pressure and initial composite temperature is determined. As the composite difference ΔXY increases, it indicates that the composite conditions are more severe, and the risk of carbon aerogel crushing or fabric deformation is higher. Therefore, the reduction range corresponding to the initial composite pressure and initial composite temperature both increase with the increase of the composite difference ΔXY. If ΔXY is less than or equal to ΔXY1, the initial composite pressure is reduced to 0.95 times its initial value based on the generated first initial composite pressure reduction command, and the initial composite temperature is reduced to 0.9 times its initial value based on the generated first initial composite temperature reduction command. Specifically, if the initial composite pressure is 0.8 MPa, the adjusted initial composite pressure is 0.76 MPa; if the initial composite temperature is 130°C, the adjusted initial composite temperature is 117°C. If ΔXY is greater than ΔXY1 and less than or equal to ΔXY2, the initial composite pressure is reduced to 0.83 times its initial value based on the generated second initial composite pressure reduction command, and the initial composite temperature is reduced to 0.85 times its initial value based on the generated second initial composite temperature reduction command. If ΔXY is greater than ΔXY2, the initial composite pressure is reduced to 0.71 times its initial value based on the generated third initial composite pressure reduction command, and the initial composite temperature is reduced to 0.8 times its initial value based on the generated third initial composite temperature reduction command. Increasing or decreasing the initial composite pressure and initial composite temperature will not have a negative impact on the preparation process of carbon fiber composite materials.

[0091] S11: Based on composite pressure and composite temperature, the initial fabric and carbon aerogel are laminated to obtain carbon fiber composite material.

[0092] Specifically, carbon aerogel is used as the core layer, and initial fabric is used to cover the upper and lower surfaces of the carbon aerogel to form a sandwich-type laminated structure of "initial fabric-carbon aerogel-initial fabric". The composite material is obtained by hot pressing according to the composite pressure and composite temperature determined in S10, which is the fireproof and heat-insulating carbon fiber of the present invention, and also has the function of infrared signal shielding.

[0093] The present invention also provides the application of the above-mentioned fire-resistant and heat-insulating carbon fiber in fire-resistant and heat-insulating fabrics. Specifically, the fire-resistant and heat-insulating fabric prepared by the carbon fiber composite material obtained by the above preparation method has infrared signal shielding function.

[0094] In this embodiment, fire-resistant and heat-insulating carbon fiber can be used as an example in the lining of fire suits. The fire-resistant and heat-insulating fabric can protect firefighters from high-temperature burns in high-temperature fire environments and reduce the infrared radiation characteristics of the outer surface of the fire suit, making it easier for thermal imaging equipment to locate and search for firefighters in dense smoke environments.

[0095] To better illustrate the preparation process of carbon fiber composite materials, the present invention will be further described below with reference to specific embodiments.

[0096] Example 1:

[0097] 25g of polyacrylonitrile copolymer was added to 75g of dimethylacetamide to obtain spinning slurry; The molar ratio of zinc chloride, 2,5-furandicarboxylic acid, and sodium hydroxide is 0.8:1.8:1.8, that is, 100 mL of zinc chloride solution, 225 mL of 2,5-furandicarboxylic acid solution, and 112.5 mL of sodium hydroxide solution are weighed out.

[0098] In this preparation, the surface bromine content B was measured to be 0.4%, therefore, it was determined to increase the preset radiation temperature. The bromine content difference ΔBX is calculated to be 0.1%, therefore, a first preset radiation temperature increase command is generated; The breaking elongation was measured to be 20%, and the textile tension was determined to be 0.8 cN / dtex. If the zinc-to-sodium concentration ratio R is found to be 0.5, it is determined that no additional zinc chloride solution or sodium hydroxide solution should be added. Calculate the rate of change of dielectric constant Δε = 1 min -1 To determine how to increase the heating rate during the carbonization process; Calculate the difference in rate of change ΔYX = 4min -1 The command to increase the third heating rate is determined. Based on the textile tension F=0.8cN / dtex, the initial composite pressure S0=0.8MPa and the initial composite temperature T0=130℃ were determined. The surface roughness M=2.1μm and the compressibility resilience H=88% were measured. The composite coefficient X=0.17 was calculated to determine the initial composite pressure and initial composite temperature. Calculate the composite offset value ΔXZ=0.33 to determine the generation of the third initial composite pressure increase command and the third initial composite temperature increase command; The carbon fiber composite material was finally prepared.

[0099] Example 2:

[0100] 30g of polyacrylonitrile copolymer was added to 70g of dimethylacetamide to obtain spinning slurry; The molar ratio of zinc chloride, 2,5-furandicarboxylic acid, and sodium hydroxide is 1:2:2, that is, 125 mL of zinc chloride solution, 250 mL of 2,5-furandicarboxylic acid solution, and 125 mL of sodium hydroxide solution are weighed out.

[0101] In this preparation, the surface bromine content B was measured to be 0.8%, therefore, the preset radiation temperature was maintained. The breaking elongation was measured to be 15%, and the textile tension was determined to be 1.0 cN / dtex. The zinc-to-sodium concentration ratio R was found to be 0.8, confirming the need to add sodium hydroxide solution. The peak areas A1 and A2 of the zinc-oxygen bond characteristic peak and the sodium-oxygen bond characteristic peak were detected. The ratio of the sodium ion characteristic peak area Q = 0.8 was calculated to determine the distributed replenishment method and the third replenishment flow rate. Calculate the rate of change of dielectric constant Δε = 17 min -1 To determine how to reduce the heating rate during the carbonization process; Calculate the rate of change offset value ΔYZ = 2min -1 The command to reduce the first heating rate is determined. Based on the textile tension F=1.0cN / dtex, the initial composite pressure S0=1.0MPa and the initial composite temperature T0=120℃ were determined. The surface roughness M=3.7μm and the compression resilience H=92% were measured. The composite coefficient X=0.6 was calculated, and the initial composite pressure and initial composite temperature were determined. The carbon fiber composite material was finally prepared.

[0102] Example 3:

[0103] 35g of polyacrylonitrile copolymer was added to 65g of dimethylacetamide to obtain spinning slurry; The molar ratio of zinc chloride, 2,5-furandicarboxylic acid, and sodium hydroxide is 1.2:2.2:2.2, that is, 150 mL of zinc chloride solution, 275 mL of 2,5-furandicarboxylic acid solution, and 137.5 mL of sodium hydroxide solution are weighed out.

[0104] In this preparation, the surface bromine content B was measured to be 2.7%, therefore, it was determined to lower the preset radiation temperature. The bromine content offset value ΔBP is calculated to be 0.2%, therefore, a second preset radiation temperature reduction command is generated; The breaking elongation was measured to be 10%, and the textile tension was determined to be 1.2 cN / dtex. The zinc-to-sodium concentration ratio R was found to be 0.2, confirming the need to replenish zinc chloride solution. The peak areas A1 and A2 of the zinc-oxygen bond characteristic peaks were detected, and the zinc ion characteristic peak area ratio P = 1.1 was calculated to determine the proportional replenishment method and the first replenishment flow rate. Calculate the rate of change of dielectric constant Δε = 10 min -1 To determine the heating rate to maintain the current carbonization process; Based on the textile tension F=1.2cN / dtex, the initial composite pressure S0=1.2MPa and the initial composite temperature T0=110℃ were determined. The surface roughness M=7.7μm and the compression resilience H=97% were measured. The composite coefficient X=1.7 was calculated to determine the initial composite pressure and initial composite temperature. Calculate the composite difference ΔXY=0.2 to determine the generation of the first initial composite pressure reduction command and the first initial composite temperature reduction command; The carbon fiber composite material was finally prepared.

[0105] Comparative Example 1: Its difference from Example 1 lies in that, based on the dielectric constant change rate Δε=1min -1 The rate of increase in temperature during the carbonization process was not determined. All other conditions were the same as in Example 1.

[0106] Comparative Example 2: The difference between this and Example 2 is that the zinc-sodium concentration ratio R was measured to be 0.8, and the addition of sodium hydroxide solution was not determined. All other conditions were the same as in Example 2.

[0107] Comparative Example 3: The difference between this and Example 3 is that the composite coefficient X was calculated to be 1.7, and the initial composite pressure and initial composite temperature were not determined. All other conditions are the same as in Example 3.

[0108] Please see Table 1 below for specific data.

[0109]

[0110] Table 1 Performance test results of Examples 1 to 3 and Comparative Examples 1 to 3 Testing and evaluation process: The fire-resistant and heat-insulating carbon fiber composite materials prepared based on the above embodiments and comparative examples were subjected to performance tests according to relevant standards: Fire resistance performance (limiting oxygen index LOI): The limiting oxygen index (%) of the sample is tested using an oxygen index tester in accordance with GB / T 5454-1997 "Test for flammability of textiles - oxygen index method".

[0111] Thermal insulation performance (thermal conductivity): According to GB / T 10295-2008 "Determination of steady-state thermal resistance and related properties of thermal insulation materials by heat flow meter method", the thermal conductivity (W / (m·K) of the sample is tested using the heat flow meter method.

[0112] Infrared signal shielding performance (infrared emissivity): According to GJB 5023.1-2003 "Test Method for Infrared Emissivity of Materials", the normal emissivity of the sample surface is measured in the 8-14μm band using an infrared emissivity meter (dimensionless, the lower the value, the better the shielding performance).

[0113] Mechanical properties (interlaminar shear strength): The interlaminar shear strength (MPa) of the composite material was tested using a universal testing machine in accordance with GB / T 1450.1-2005 "Test method for interlaminar shear strength of fiber reinforced plastics".

[0114] Interfacial peel strength: According to GB / T 2792-2014 "Test method for peel strength of adhesive tape", the interfacial peel strength (N / cm) between the initial fabric and carbon aerogel was tested using the 90° peel method. This indicator directly quantifies the interfacial bonding quality of the laminated composite.

[0115] Thermal insulation temperature difference: Based on a self-developed testing method, the sample is placed on a 300℃ heat source with a thickness of 5mm. The temperature difference between the back side and room temperature after 30 minutes of stable temperature is recorded as the thermal insulation temperature difference (℃). This indicator directly reflects the comprehensive protective capability of the fabric in actual high-temperature environments.

[0116] Results analysis: As shown in Table 1, the fire-resistant and heat-insulating carbon fiber composite materials prepared using the complete intelligent dynamic control method of the present invention (Examples 1 to 3) are significantly better than those of Comparative Examples 1 to 3 that did not implement the partial control strategy in all key performance indicators.

[0117] Pre-oxidation and textile control: In Example 1, the surface bromine content B was detected to be 0.4% (below the lower limit of 0.5%). The preset radiation temperature was promptly increased and the first heating command was executed, ensuring sufficient pre-oxidation and good fiber structure transformation. In Comparative Example 1, the heating rate was not increased when the dielectric constant change rate was abnormal, resulting in insufficient carbonization and significantly lower LOI and interlaminar shear strength.

[0118] Coordination reaction control: In Example 2, the zinc-sodium concentration ratio R was found to be 0.8 (higher than the upper limit). Sodium hydroxide solution was added in time, and distributed addition was adopted by using the sodium ion characteristic peak area ratio Q=0.8 to maintain the stoichiometry of the coordination polymer. After carbonization, the aerogel structure was intact, and the interfacial peel strength reached 4.2 N / cm. In Comparative Example 2, no sodium hydroxide was added, resulting in incomplete coordination of the product and an interfacial peel strength of only 3.3 N / cm, which affected the thermal insulation performance of the composite material.

[0119] Carbonization process control: Example 1 detected a dielectric constant change rate Δε = 1 min -1 (Far below the lower limit), by calculating ΔYX=4min -1 The third heating rate increase command was triggered, increasing the heating rate to 1.4 times, allowing the carbonization reaction to proceed fully. This resulted in a uniform aerogel pore structure, a thermal conductivity as low as 0.032 W / (m·K), and a thermal insulation temperature difference as high as 152℃. Comparative Example 1 also measured Δε = 1 min. -1 However, the heating rate was not increased, resulting in insufficient carbonization conversion, a thermal conductivity as high as 0.048 W / (m·K), a thermal insulation temperature difference of only 112℃, and deterioration of thermal insulation performance.

[0120] Laminated Composite Matching: In Example 3, the composite coefficient X was calculated to be 1.7 (greater than the upper limit of 1.5). A first reduction command was triggered by ΔXY=0.2, reducing the composite pressure from 1.2 MPa to 1.14 MPa and the composite temperature from 110℃ to 99℃, preventing the carbon aerogel from collapsing. The interlaminar shear strength reached 30.1 MPa, and the interfacial peel strength was as high as 5.1 N / cm. In Comparative Example 3, without reducing the composite parameters, the aerogel structure was destroyed, with an interlaminar shear strength of only 24.1 MPa and an interfacial peel strength of only 3.6 N / cm, indicating a significant decrease in interfacial bonding quality.

[0121] Overall Performance: Examples 1 to 3, through closed-loop control of multiple parameters throughout the entire process, resulted in final products that combined high fire resistance (LOI ≥ 31.8%), excellent thermal insulation (thermal conductivity ≤ 0.035 W / (m·K), thermal insulation temperature difference ≥ 143℃), infrared shielding capability (emissivity ≤ 0.24), and high interfacial bonding strength (interlaminar shear strength ≥ 26.3 MPa, interfacial peel strength ≥ 4.2 N / cm). The comparative example, lacking key control steps, showed significant deterioration in all performance aspects, failing to meet the requirements for high-performance protective materials.

[0122] In summary, this invention effectively solves key technical challenges in the preparation of carbon fiber composite materials by introducing real-time feedback and intelligent control based on multiple parameters such as surface bromine content, zinc-sodium concentration ratio, characteristic peak area ratio, dielectric constant change rate, surface roughness, and compression rebound rate. This significantly improves the overall performance of the product and has outstanding industrial application value.

[0123] All technologies not mentioned in the above embodiments are existing technologies. It is understood that no specific limitation is made to any preset parameter or critical parameter in the embodiments of the present invention, and the above values ​​are not limited thereto. Those skilled in the art can adjust the preset parameters or critical parameters accordingly based on actual needs, analysis of historical data, or equipment usage.

[0124] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will all fall within the scope of protection of the present invention.

Claims

1. A method for preparing fire-resistant and heat-insulating carbon fiber, characterized in that, include: Polyacrylonitrile copolymer is dissolved in dimethylacetamide solution to obtain spinning slurry, and then spun and stretched to produce fiber filaments; The fiber filaments were placed in a gas mixture of oxygen and hydrogen bromide and pre-oxidized at a preset radiation temperature. The surface bromine content during the pre-oxidation process is detected, and based on the comparison with the preset bromine content, it is determined whether to adjust the preset radiation temperature to obtain pre-oxidized fibers. The breaking elongation of the pre-oxidized fiber was detected and the pre-oxidized fiber was spun based on a determined textile tension to form an initial fabric, and the surface roughness was determined. The dimethylacetamide solution, zinc chloride solution, and sodium hydroxide solution are mixed, and a coordination reaction is carried out at a preset coordination temperature. The zinc-sodium concentration ratio is determined based on the ratio of zinc ion concentration to sodium ion concentration during the coordination reaction, and the characteristic peak area ratio of the corresponding ions is determined based on the zinc-oxygen bond and the sodium-oxygen bond. The zinc chloride solution or the sodium hydroxide solution is added based on the zinc-sodium concentration ratio and the preset zinc-sodium concentration ratio, and the addition flow rate and addition method are determined based on the characteristic peak area ratio of the corresponding ions and the corresponding preset characteristic peak area ratio to obtain the bimetallic coordination polymer. The bimetallic coordination polymer was carbonized under a protective atmosphere to obtain a carbon aerogel, and the compression resilience was determined. The composite pressure and composite temperature are determined based on the surface roughness and the compression resilience, and the initial fabric and the carbon aerogel are laminated together to obtain a carbon fiber composite material.

2. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 1, characterized in that, The process of adding the zinc chloride solution or the sodium hydroxide solution includes: Based on the fact that the zinc-sodium concentration ratio is less than the lower limit of the preset zinc-sodium concentration ratio, it is determined that the zinc chloride solution should be added. Based on the fact that the zinc-sodium concentration ratio is greater than the upper limit of the preset zinc-sodium concentration ratio, it is determined that the sodium hydroxide solution should be added.

3. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 2, characterized in that, The process of determining the supplementary flow and the supplementary method includes: If it is determined that the zinc chloride solution will be added, the characteristic peak area ratio of the corresponding ions will be determined as the characteristic peak area ratio of zinc ions; Based on the fact that the zinc ion characteristic peak area ratio is less than or equal to the preset zinc ion characteristic peak area ratio, a proportional replenishment method and a first replenishment flow rate are determined, and the first replenishment flow rate is determined based on the difference in zinc ion characteristic peak area. Based on the fact that the area ratio of the zinc ion characteristic peaks is greater than the preset area ratio of the zinc ion characteristic peaks, a uniform replenishment method and a second replenishment flow rate are determined.

4. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 2, characterized in that, The process of determining the supplementary flow and the supplementary method also includes: If it is determined that the sodium hydroxide solution will be added, the characteristic peak area ratio of the corresponding ions will be determined to be the characteristic peak area ratio of sodium ions; Based on the fact that the sodium ion characteristic peak area ratio is less than or equal to the preset sodium ion characteristic peak area ratio, a distributed replenishment method and a third replenishment flow rate are determined, and the third replenishment flow rate is determined based on the sodium ion characteristic peak area difference. Based on the fact that the sodium ion characteristic peak area ratio is greater than the preset sodium ion characteristic peak area ratio, a uniform replenishment method and a fourth replenishment flow rate are determined.

5. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 1, characterized in that, The process of determining the composite pressure and composite temperature includes: The roughness difference is determined based on the absolute value of the difference between the surface roughness and the preset roughness, and the springback difference is determined based on the absolute value of the difference between the compression springback rate and the preset springback rate. The composite coefficient is calculated based on the roughness difference and the springback difference.

6. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 5, characterized in that, The process of determining the composite pressure and composite temperature also includes: The initial composite pressure and initial composite temperature are determined based on the textile tension. Based on the fact that the composite coefficient is less than the lower limit of the preset composite coefficient, it is determined to increase the initial composite pressure and the initial composite temperature, and the increase in the initial composite pressure and the initial composite temperature are both positively correlated with the composite offset value. Based on the comparison results of the composite coefficient being greater than the upper limit of the preset composite coefficient, it is determined to reduce the initial composite pressure and the initial composite temperature, and the reduction of the initial composite pressure and the initial composite temperature are both positively correlated with the composite difference.

7. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 1, characterized in that, The process for obtaining carbon aerogel includes: The dielectric constant of the bimetallic coordination polymer was detected at several time points during the carbonization process to obtain the rate of change of dielectric constant. Based on the fact that the rate of change of the dielectric constant is less than the lower limit of the preset rate of change, the heating rate in the carbonization process is increased, and the increase in the heating rate is positively correlated with the difference in the rate of change. Based on the fact that the rate of change of the dielectric constant is greater than the upper limit of the preset rate of change, the heating rate during the carbonization process is reduced, and the reduction in the heating rate is positively correlated with the offset value of the rate of change.

8. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 1, characterized in that, The process of determining whether to adjust the preset radiation temperature includes: Based on the comparison results of the surface bromine content being less than the lower limit of the preset bromine content, it is determined to increase the preset radiation temperature; Based on the comparison results of the surface bromine content being greater than the upper limit of the preset bromine content, it is determined to reduce the preset radiation temperature.

9. The method for preparing fire-resistant and heat-insulating carbon fiber according to claim 8, characterized in that, The preset radiation temperature is increased based on the comparison between the difference in bromine content and the preset difference in bromine content, and the increase in the preset radiation temperature is positively correlated with the difference in bromine content. The preset radiation temperature is reduced based on the comparison between the bromine content offset value and the preset bromine content offset value, and the reduction in the preset radiation temperature is positively correlated with the bromine content offset value.

10. The application of fire-resistant and heat-insulating carbon fiber in fire-resistant and heat-insulating fabrics, characterized in that, The carbon fiber composite material is prepared by the preparation method described in any one of claims 1-9, and the fireproof and heat-insulating fabric prepared based on the carbon fiber composite material has an infrared signal shielding function.

Citation Information

Patent Citations

  • Flame-retardant and heat-insulating composite fiber fabric, preparation method thereof and application of flame-retardant and heat-insulating composite fiber fabric in fireproof suit

    CN117944337A